1993
DOI: 10.1111/j.1745-3984.1993.tb00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Performance Assessments: Strategies for Managing Local Item Dependence

Abstract: Performance assessments appear on a priori grounds to be likely to produce far more local item dependence (LID) than that produced in the use of traditional multiple‐choice tests. This article (a) defines local item independence, (b) presents a compendium of causes of LID, (c) discusses some of LID's practical measurement implications, (d) details some empirical results for both performance assessments and multiple‐choice tests, and (e) suggests some strategies for managing LID in order to avoid negative measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
535
1
26

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 543 publications
(574 citation statements)
references
References 15 publications
12
535
1
26
Order By: Relevance
“…This implies that there are no dependencies between the items except those attributed to the latent trait (Marais & Andrich, 2008;Yen, 1993). Violations of local independence may be indicated by residual correlations and multidimensionality (Ip, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This implies that there are no dependencies between the items except those attributed to the latent trait (Marais & Andrich, 2008;Yen, 1993). Violations of local independence may be indicated by residual correlations and multidimensionality (Ip, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A critical assumption is that the items are conditionally independent. This assumption is unlikely to be true if a number of items are related to one another through reference to a common stem, for such structures foster local dependence (Yen, 1993). Reading comprehension and listening comprehension testlets, as previously described, are examples of structures that are likely to yield local dependence.…”
Section: + + +mentioning
confidence: 97%
“…For example, the skills or competencies that students demonstrate during a PBA are rated by one or more raters, usually resulting in a categorization of competency mastery as, for instance, insufficient/sufficient. However, it has often been demonstrated that PBAs score low on generalizability, reliability, and standardization, and that rater effects can influence students' scores (Kane 1990;Linn et al 1991;Ruiz-Primo et al 1993;Shavelson et al 1993;Yen 1993;Messick 1995;Dekker and Sanders 2008). MBPA might be used as an alternative and improved approach to the measurement of vocational skills.…”
Section: Introductionmentioning
confidence: 99%